2017
DOI: 10.1038/s41598-017-08408-w
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of Glanzmann variants of Calf-1 domain of αIIbβ3 integrin revealed dynamic allosteric effect

Abstract: Integrin αIIbβ3 mediates platelet aggregation and thrombus formation. In a rare hereditary bleeding disorder, Glanzmann thrombasthenia (GT), αIIbβ3 expression / function are impaired. The impact of deleterious missense mutations on the complex structure remains unclear. Long independent molecular dynamics (MD) simulations were performed for 7 GT variants and reference structure of the Calf-1 domain of αIIb. Simulations were analysed using a structural alphabet to describe local protein conformations. Common an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 50 publications
(61 reference statements)
2
73
0
Order By: Relevance
“…Recently, Van Belleghem et al . 25 have shown that human immune responses to phages in vitro are predominantly anti‐inflammatory and – interestingly – moderate amounts of endotoxin can up‐regulate those effects further. The authors have shown that adding an intermediate level of endotoxin up‐regulates interleukin‐1 receptor antagonist and reduces strongly the expression of proinflammatory cytokines chemokine (C‐X‐C motif) ligand 1 (CXCL1) and CXCL5.…”
Section: Phages As Anti‐inflammatory Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Van Belleghem et al . 25 have shown that human immune responses to phages in vitro are predominantly anti‐inflammatory and – interestingly – moderate amounts of endotoxin can up‐regulate those effects further. The authors have shown that adding an intermediate level of endotoxin up‐regulates interleukin‐1 receptor antagonist and reduces strongly the expression of proinflammatory cytokines chemokine (C‐X‐C motif) ligand 1 (CXCL1) and CXCL5.…”
Section: Phages As Anti‐inflammatory Agentsmentioning
confidence: 99%
“…Recent findings indicate that phages induce IL‐10 production by human mononuclear cells 25. This cytokine, known for its anti‐inflammatory action, has been recognized as playing a protective role against hepatic injury.…”
Section: Phages In Potential Immunotherapy Of Aldmentioning
confidence: 99%
See 2 more Smart Citations
“…Arg755 localizes to the upper end of a β‐strand with its side chain aligning toward the exterior limiting the short range structural effect within αIIb of its substitution by Gln or Pro. Significantly, long‐range effects were recently identiffied for these substitutions from molecular dynamics simulations (Goguet, Narwani, Petermann, Jallu, & De Brevern, ). The jury is out on whether the relatively inert Leu752Val contributes to the type I GT phenotype.…”
Section: Resultsmentioning
confidence: 99%